2013
DOI: 10.1007/s00464-012-2695-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of robotic general surgery course on participants’ surgical practice

Abstract: Background Courses, including lectures, live surgery, and hands-on session, are part of the recommended curriculum for robotic surgery. However, for general surgery, this approach is poorly reported. The study purpose was to evaluate the impact of robotic general surgery course on the practice of participants. Methods Between 2007 and 2011, 101 participants attended the Geneva International Robotic Surgery Course, held at the University Hospital of Geneva, Switzerland. This 2-day course included theory lecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…12 Training programmes Robotic training programmes which use a combination of tutorials, observation of live surgery and skills training with simulation have been described (see Figure 2). 11,14,16,17 The Fundamental Skills in Robotic Surgery (FSRS) training programme was created using curriculum exercises from the Fundamentals of Laparoscopic Surgery (FLS) course. A short tutorial on the usage of the Da Vinci Surgical Simulator (DvSS) was followed by three main skills tests; suture pass, ball skills and 4th arm manipulation.…”
Section: Simulation Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Training programmes Robotic training programmes which use a combination of tutorials, observation of live surgery and skills training with simulation have been described (see Figure 2). 11,14,16,17 The Fundamental Skills in Robotic Surgery (FSRS) training programme was created using curriculum exercises from the Fundamentals of Laparoscopic Surgery (FLS) course. A short tutorial on the usage of the Da Vinci Surgical Simulator (DvSS) was followed by three main skills tests; suture pass, ball skills and 4th arm manipulation.…”
Section: Simulation Trainingmentioning
confidence: 99%
“…Participants who had completed the course went on to practice robotic surgery in 46% of cases whereas only 6% did so pre-course. 17 For more advanced training and education Rashid et al have presented their approach to robotic training in a fellowship setting beginning with Da Vinci certification followed by Volume stepwise introduction of practical hands on experience in the steps of prostatectomy with progress measured using a 1-5 analogue scale. Each assessment was logged in a digitally maintained diary.…”
Section: Simulation Trainingmentioning
confidence: 99%
“…The da Vinci Standard surgical system was introduced early in the twentieth century. This robotic system was used in some field of surgery as urology, digestive surgery, and cardiothoracic surgery [5,6]. The next-generation surgical system was introduced in the following years with field indications were enlarged as follows: general surgery, gynecology, and otolaryngology.…”
Section: Roboticmentioning
confidence: 99%
“…It was found that the use of robotic surgery increased rapidly across numerous different procedures after hospitals begin performing robotic surgery. This trend was associated with a decrease in the use of laparoscopic minimally invasive procedures, which for most surgeons was already considered a safe and effective approach when clinically feasible [5,6]. The advent of robotic surgery has certainly brought further advances in the field of mini-invasive surgery.…”
Section: Roboticmentioning
confidence: 99%
“…In the last few years, robotically assisted techniques have also increasingly been used for resections of the colon and rectum . Robotic techniques were developed to overcome some of the limitations of conventional laparoscopic instruments by providing increased range and precision of instrument movements, a stable camera position with magnified three‐dimensional imaging and avoidance of the fulcrum effect .…”
Section: Introductionmentioning
confidence: 99%